Temperature influence on matric suction in unsaturated soils: experimental insights - Feifei Liu; Cheng Xu; Mingming Ba; Xuesong Mao (Scientific Reports)
Abstract Temperature is a critical factor affecting the matric suction of unsaturated soils. This study employed a simple and time-saving method to investigate the influences of temperature and moisture content on the temperature dependence of matric suction in loess and sand soils. Based on experimental data, the fitting performance of three data-fitting models-Brooks-Corey, van Genuchten, and Fredlund-Xing -was evaluated at temperatures above 0 °C. The results indicated that matric suction decreased as temperature increased. The variation of matric suction with temperature was categorized into the maximum value range (RMax), the highly temperature sensitive range (RTS) and the weak temperature sensitive range (RTW). Additionally, RMax and RTW were observed to decrease and increase, respectively, as moisture content increased. Above 0 °C, the sensitivity of matric suction to temperature decreased with increasing moisture content, while below 0 °C, temperature sensitivity increased as moisture content increased. Furthermore, the matric suction of loess showed greater sensitivity to temperature changes than that of sand. The van Genuchten model outperformed the other models at temperatures above 0 °C. This study provides experimental evidence for a deeper understanding of the impact of temperature changes on matric suction.